Blocking NMDA receptor at rest: a possible alleviation of depression - Lu Wei (Acta Pharmacologica Sinica, 2016)
D epression is a common but serious illness, which is described as a state of low mood or mood disorder that involves feelings of sadness lasting for two weeks or longer[1]. Depressed people may suffer from a spectrum of syndromes, including change of sleep habitation or pattern, dramatic weight loss, cognitive impairments or even suicide. One conventional antidepressant medication is selective serotonin re-uptake inhibitor[2, 3]. However, the weeks delay of its efficacy constitutes the major drawback of this treatment[3]. Therefore, fast-acting antidepressants are urgently needed for clinical treatment of depression. Autry et al. reported in a recent issue of Nature that N-methyl-D-aspartate receptor (NMDAR) antagonists could be such candidates by triggering rapid behavioural antidepressant responses[4].